Reliability-Oriented Design of Inverter-Fed Low-Voltage Electrical Machines: Potential Solutions - Yatai Ji; Paolo Giangrande; Vincenzo Madonna; Weiduo Zhao; Michael Galea (Energies, 2021)
Transportation electrification has kept pushing low-voltage inverter-fed electrical machines to reach a higher power density while guaranteeing appropriate reliability levels. Methods commonly adopted to boost power density (i.e., higher current density, faster switching frequency for high speed, and higher DC link voltage) will unavoidably increase the stress to the insulation system which leads to a decrease in reliability. Thus, a trade-off is required between power density and reliability during the machine design. Currently, it is a challenging task to evaluate reliability during the design stage and the over-engineering approach is applied. To solve this problem, physics of failure (POF) is introduced and its feasibility for electrical machine (EM) design is discussed through reviewing past work on insulation investigation. Then the special focus is given to partial discharge (PD) whose occurrence means the end-of-life of low-voltage EMs. The PD-free design methodology based on understanding the physics of PD is presented to substitute the over-engineering approach. Finally, a comprehensive reliability-oriented design (ROD) approach adopting POF and PD-free design strategy is given as a potential solution for reliable and high-performance inverter-fed low-voltage EM design.